N6-Methyladenosine (m6A): A Promising New Molecular Target in Acute Myeloid Leukemia - Ianniello, Zaira; Paiardini, Alessandro; Fatica, Alessandro (Frontiers in Oncology, 2019)
Recent studies have uncovered an important role for RNA modifications in gene expression regulation, which led to the birth of the epitranscriptomics field. It is now acknowledged that RNA modifiers play a crucial role in the control of differentiation of stem and progenitor cells and that changes in their levels are a relevant feature of different types of cancer. To date, among more than 160 different RNA chemical modifications, the more relevant in cancer biology is the reversible and dynamic N6-methylation of adenosine, yielding N6-methyladenosine (m6A). m6A is the more abundant internal modification in mRNA, regulating the expression of the latter at different levels, from maturation to translation. Here, we will describe the emerging role of m6A modification in acute myeloid leukemia (AML), which, among first, has demonstrated how mis-regulation of the m6A modifying system can contribute to the development and progression of cancer. Moreover, we will discuss how AML is paving the way to the development of new therapeutic options based on the inhibition of m6A deposition.